Field deployable trace radioisotope analysis through combined electrochemical and alpha spectroscopy methods - Giglio, Daryl; Cho, Sung Gu; Oksuz, Ibrahim; Remy, Jarod; Kandlakunta, Praneeth; Hlinka, Vasil; Downing, Greg; Co, Anne C.; Cao, Lei R. (Journal of radioanalytical and nuclear chemistry, 2025)
A method for depositing actinides directly onto a 4H-SiC Schottky barrier diode (SBD) detector as a field deployable actinides sensor was developed to enable off-site analysis, shortening the time to obtain critical information such as elements, concentration, and/or isotopic ratio related to the radiological situation. A thin film of Hg was first electrodeposited onto the Pt contact of the SiC diode, followed by chronoamperometric deposition of microgram levels of actinides under conventional control conditions. The 4H-SiC diode maintained consistent functionality through the electrodeposition process and showed resolved alpha-energy spectra that contained accurate isotopic information demonstrating the feasibility of a combined chemical and radiological sensor for field actinide detection and quantification.